Society seen as a victim — how it may affect criminal law - Hryniewicz-Lach, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Crimes committed against individual victims quite often affect the whole of society or a certain community as well. Therefore society should be seen as a relevant subject on the victim’s side, and not only as a potential offender or a neutral third party providing certain services for individual victims. Regarding society as a kind of a victim enables us to see crime and criminal reaction in a broader context going beyond the interests of individuals and creating a counterweight to them. For this reason it is important to see in which way society can be victimised, what are its preventive and compensatory interests and how they can be satisfied with the instruments of criminal law.
Keywords: ofiara; odszkodowanie; zapobieganie; prawo karne